2010
DOI: 10.4049/jimmunol.1002188
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Astrocyte-Derived IL-15 to CD8 T Cell Effector Functions in Multiple Sclerosis

Abstract: The contribution of local factors to the activation of immune cells infiltrating the CNS of patients with multiple sclerosis (MS) remains to be defined. The cytokine IL-15 is pivotal in the maintenance and activation of CD8 T lymphocytes, a prominent lymphocyte population found in MS lesions. We investigated whether astrocytes are a functional source of IL-15 sufficient to enhance CD8 T lymphocyte responses and whether they provide IL-15 in the inflamed CNS of patients with MS. We observed that human astrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
90
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 79 publications
8
90
0
Order By: Relevance
“…Recent findings suggest that astrocytes play an active role during demyelination and oligodendrocyte degeneration by controlling local inflammation in the CNS, which damages OLs and axons [33] . Astrocyte production of IL-15 leads to the activation of CD8 T-lymphocytes that contribute to the exacerbation of tissue damage during MS [34] . Recent studies also suggest that aberrant upregulation of astroglial ceramide potentiates OL injury [35,36] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggest that astrocytes play an active role during demyelination and oligodendrocyte degeneration by controlling local inflammation in the CNS, which damages OLs and axons [33] . Astrocyte production of IL-15 leads to the activation of CD8 T-lymphocytes that contribute to the exacerbation of tissue damage during MS [34] . Recent studies also suggest that aberrant upregulation of astroglial ceramide potentiates OL injury [35,36] .…”
Section: Discussionmentioning
confidence: 99%
“…In MS patients, both soluble and membrane-bound IL-15 levels are increased in the serum and cerebrospinal fluid (29)(30)(31). Recently, increased IL-15 expression was found on peripheral B cells and on astrocytes within brain lesions of MS patients, compared with control subjects (24,32). The cytotoxicity-enhancing effect of IL-15 has already been described for NK cells and CD8 + T cells (24,(32)(33)(34).…”
mentioning
confidence: 86%
“…Recently, increased IL-15 expression was found on peripheral B cells and on astrocytes within brain lesions of MS patients, compared with control subjects (24,32). The cytotoxicity-enhancing effect of IL-15 has already been described for NK cells and CD8 + T cells (24,(32)(33)(34). Specifically, it was shown that the signaling pathways of IL-15 and the activating NK cell receptor NKG2D are intertwined (35).…”
mentioning
confidence: 99%
“…In addition to T cell anergy, activation-induced cell death and the proapoptotic molecule Bim keep autoreactive CD8 + T cells in check (19)(20)(21). Extrinsic mechanisms also operate to repress self-reactive T cells; these include availability of cytokines, such as IL-7 and IL-15 (22,23), and the suppressive effect of regulatory T cells through their ability to secrete IL-10 and TGF-b (24). Although IFN-g was shown to promote CD8 + T cell apoptosis during viral infection (25), a role for IFN-g in the regulation of self-reactive CD8 + T cell effectors has not been described.…”
Section: Cd8 + T Cells Responding To Viral Infections Initiate Their mentioning
confidence: 99%